If it's not what You are looking for type in the equation solver your own equation and let us solve it.
12=8-3(n-1)
We move all terms to the left:
12-(8-3(n-1))=0
We calculate terms in parentheses: -(8-3(n-1)), so:We get rid of parentheses
8-3(n-1)
determiningTheFunctionDomain -3(n-1)+8
We multiply parentheses
-3n+3+8
We add all the numbers together, and all the variables
-3n+11
Back to the equation:
-(-3n+11)
3n-11+12=0
We add all the numbers together, and all the variables
3n+1=0
We move all terms containing n to the left, all other terms to the right
3n=-1
n=-1/3
n=-1/3
| 1+5n=-7+4n-5n | | -2=f+13 | | 4-2x-x+7=x+3+4 | | z/3+6=7 | | 12x-30=8x+26 | | -x+6+2x=4x-4 | | x-2(-4)=6 | | 47-k=34 | | G(x)=2x^2+x-6 | | -6/n=3 | | -3(8+3x)=-87 | | 2x-0.4=113.4 | | 5(7n-1)+4=31+3n | | -(9/4)v+4/5=7/8 | | 4d-11=15-19d | | 4x+6x+15=55 | | (t^2+4t+4)^2=0 | | 9x-15-2x=3(-20+30x) | | -8=12-x/4 | | 3.2a–16=4a | | q+109=q+89 | | f(-1)=|-1|+2 | | (2t+2)/3-(5t)/4=11/6 | | 300=12x+85 | | -12=c-2 | | 5n(7n-1)+4=31+3n | | 0.70n-23=0.50n-19 | | 3x-2x/8=8 | | -6(1x-2)=24 | | 9(5h-4)=54 | | 3x+18+2x=68 | | K/5+3k=-3 |